(untitled) (Eurasian Research Bulletin, 2023)
Upper gastrointestinal bleeding (UGIB) is a significant medical disorder that can be brought on by a variety of things, including medications. An adverse event resulting in UGIB as a consequence of the use of certain medications can cause significant illness and impermanence in patients. This article sets out to offer an overview of the most commonly prescribed drugs that are associated with UGIB as well as their mechanism of action so that they can be better understood